Relationships between nursing leadership and organizational, staff and patient outcomes: A systematic review of reviews - Hult Marja; Terkamo-Moisio Anja; Kaakinen Pirjo; Karki Suyen; Nurmeksela Anu; Palonen Mira; Peltonen Laura-Maria; Häggman-Laitila Arja (WILEY, 2025)
Aim
To assess and describe reviews of nursing leadership styles associated with organizational, staff and patient outcomes.
Design
A systematic review of reviews.
Methods
Reviews describing a search strategy and quality assessment. The review followed the PRISMA statement. Nine databases were searched in February 2022. ResultsAfter screening 6992 records, 12 reviews were included reporting 85 outcomes for 17 relational, nine task-oriented, five passive and five destructive leadership styles. Transformational leadership, which is one of the relational styles, was the most studied among all the styles. Of the outcomes, staff outcomes were the most reported, notably job satisfaction, and patient outcomes were less reported. Also, mediating factors between relational leadership styles and staff and patient outcomes were identified.
Conclusion
Extensive research shows the beneficial impacts of relational leadership; however, destructive leadership research is lacking. Relational leadership styles should be conceptually assessed. More research is needed on how nurse leadership affects patients and organizations.